Existence of Registered/Unregistered Marriage Clauses in Family Cards from a Family Law Perspective - Yenny Febrianty; Sulastri Sulastri; Zulfiani Zulfiani (Faculty of Law, Universitas Pekalongan, 2023)
Family plays a central role in maintaining the stability and continuity of a nation, and marriage is the primary foundation for forming a legally recognized family. The Family Card records marital status and holds a crucial role in family administration and the legal rights of family members. However, practices in the field often do not align with the rules of recording marriages in the Family Card. This research aims to examine the influence of marriage clauses in the Family Card on the legal status of marriage from the perspective of family law, as well as its impacts in the social context. Using a normative legal research method, with a legislative approach and data from relevant legal documents, this study contributes to understanding and addressing family law issues in Indonesia while adapting to the diverse social and religious realities of the community. The research findings show that recording marriage in the Family Card has a significant impact from the perspective of family law in Indonesia. Recorded status in the Family Card provides legal certainty, better legal protection, and easier access to rights and benefits. Conversely,